Approaching the Promise of 5G - Campbell, Leith H. (Journal of Telecommunications and the Digital Economy, 2021)
This editorial comes in two parts: some remarks on fulfilling the promise of 5G as it rolls out; and a brief introduction to the papers in this issue.